Variations among glioblastoma cell lines in boron-mediated enhancement of cell killing by proton beams - Oldřich Zahradníček; Pavel Kundrát; Irina Danilova; Pavel Bláha; Kateřina Pachnerová Brabcová; Anna Jelínek Michaelidesová; Jaroslav Šolc; Jana Vachelová; Matěj Navrátil; Vladimír Vondráček; Lucie Dyčková; Marie Davídková (Scientific Reports)
Abstract Enhancement in cell killing by proton beams in the presence of boron (natural mixture natB: 80% 11B, 20% 10B) was reported, selectively in the Bragg peak region, putatively due to the proton-11B capture reaction. However, as some groups observed no such enhancement or assigned it to secondary neutron-10B capture, proton-boron capture therapy (PBCT) remains controversial. We previously validated this concept for U-87 MG glioblastoma cells. To test its generality and potential applicability for these tumours, we assessed PBCT using three further cell lines widely used in glioblastoma research. In U251 cells, natB enhanced cell killing by protons in Bragg peak but also in plateau regions, effects of 10B were even higher, and were found also for 18MV but not 6 MV photon beams (above and below photo-neutron production thresholds, respectively), suggesting a key role of secondary neutrons. For A172 and T98G cells, no enhancement was found at all. This variability among cell lines may stem from differences in boron uptake and/or in intercellular signalling likely needed to amplify the initial events in a few hit cells to population-level effects. Together with recent negative studies, the results suggest that potential clinical applications of PBCT are less promising than originally thought.